O supervisor de ensino e os desafios da formação continuada do diretor de escola SESI - Santos, Elma dos (2017)
The present study had the general objective to investigate if and how the teaching supervisor of SESI-SP contributes to the continued formation of the school director. The theoretical methodological path is based on a qualitative perspective, which made it possible to use data analysis from the approach proposed by André (1983) called "prose analysis", considered by the author as a way to investigate the meaning of qualitative data. The data, made available to the participants via Google Drive, have been collected through questionnaires, which supported the characterization of the two groups of subjects: 152 school directors and 15 teaching supervisors. Although it was previously intentional, only after the application of the questionnaire that had as a specific objective to identify the contributions of the supervisor of teaching in the student's learning and training, has it been suggested to the teaching supervisors the participation in a discussion group, following the one indicated by WELLER (2006). The theoretical framework has been developed from the discussions proposed by Socio-Historical Psychology, in addition to studies on school management, supervision of teaching and continuing education. The result have showed that the teacher's supervisor contributes to the continued formation of school principals when it is performed in a critical and collaborative way, based on realities experienced in the school space